Intracranial cryptococcosis in immunocompromised patients: CT and MR findings in 29 cases. - Tien, R D; Chu, P K; Hesselink, J R; Duberg, A; Wiley, C (American Journal of Neuroradiology, 1991)
CT and MR scans of 29 immunocompromised patients (28 with AIDS or ARC, one with diabetes mellitus) who had documented intracranial cryptococcal infection were reviewed retrospectively. All patients had CT studies; 26 received iodinated contrast agent. CT findings included normal results in nine of 29, atrophy only in 13 of 29, nonenhancing lesions in three of 29, enhancing lesions in two of 20, and foci of leptomeningeal calcification in two of 29. Ten patients had both CT and MR studies, and four received gadopentetate dimeglumine. Among these 10 patients, five had normal CT studies and one showed moderate central atrophy. All 10, however, had abnormal MR findings. We observed four patterns: (1) parenchymal cryptococcoma (3/10); (2) numerous clustered tiny foci that were hyperintense on T2-weighted images and non-enhancing on postcontrast T1-weighted images, located relatively symmetrically in the basal ganglia bilaterally and in midbrain, representing dilated Virchow-Robin spaces (4/10); (3) multiple miliary enhancing parenchymal and leptomeningeal nodules (1/10); and (4) a mixed pattern, consisting of dilated Virchow-Robin spaces with mixed lesions such as cryptococcoma and miliary nodules (2/10). In the group of six patients with dilated Virchow-Robin spaces (patterns 2 and 4), two received gadopentetate dimeglumine, but the Virchow-Robin space lesions did not enhance; among the remaining four patients, two received gadopentetate dimeglumine (one with pattern 1 and one with pattern 3) and the lesions did enhance. Three patients in our study subsequently died and autopsies were performed. The postmortem results revealed dilated Virchow-Robin spaces filled with fungi in the basal ganglia, which correlated well with MR findings.(ABSTRACT TRUNCATED AT 250 WORDS)